Water permeability of polyunsaturated lipid membranes measured by 17O NMR. - Huster, D (1997)
Diffusion-controlled water permeation across bilayers of polyunsaturated phospholipids was measured by 17O nuclear magnetic resonance. In 100-nm extruded liposomes containing 50 mM MnCl2, water exchange between internal and external solutions was monitored via changes in the linewidth of the 17O water resonance of external water. Liposome size and shape were characterized by light scattering methods and determination of liposome trapped volume. At 25 degrees C, the following water permeability coefficients were determined: 18:0-18:1n-9 PC, 155 +/- 24 microns/s; 18:0-18:3n-3 PC, 330 +/- 88 microns/s; and 18:0-22:6n-3 PC, 412 +/- 91 microns/s. The addition of 1 M ethanol reduced permeability coefficients to 66 +/- 15 microns/s for 18:0-18:1n-9 PC and to 239 +/- 67 microns/s for 18:0-22:6n-3 PC. Furthermore, the addition of 50 mol% 18:1n-9-18:1n-9 PE reduced the water permeability from 122 +/- 21 microns/s for pure 18:1n-9-18:1n-9 PC to 74 +/- 15 microns/s for the mixture. The significant increase in water permeation for membranes with polyunsaturated hydrocarbon chains correlates with looser packing of polyunsaturated lipids at the lipid-water interface and the suggested deeper penetration of water into these bilayers. Ethanol may block water diffusion pathways by occupying points of water entry into bilayers at the interface. The addition of dioleoylphosphatidylethanolamine increases lipid packing density and, consequently, reduces permeation rates.